2018
DOI: 10.1002/mats.201700103
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of Cross‐Linked Phenolic Resins Using a United‐Atom Model

Abstract: because of their excellent physical properties such as mechanical strength, electrical insulation, heat resistance, and solvent resistance. [1] These properties result from their highly cross-linked network structures, which comprise phenolic and methy lene units. In these structures, three methylenes can connect to a phenolic ring such that one can be at the para (p) and two can be at the ortho (o) positions that are adjacent to the hydroxyl group of the phenolic ring, as shown in Figure 1. To further improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…4. a, Comparison of an 13 C NMR spectrum (HPE in DMF [45]) and the predicted degree distribution for the system with A 2 :B 3 = 1:1 at p A = 0.93. b, Comparison of the phenolic unit degree distribution (only out-edges) in a phenol-methylene system predicted by MD (dots) simulation [30] to the theory (solid lines). The gel point is predicted at p A = 0.58 by the MD simulation, the theory predicts it at p A = 0.5.…”
Section: The Time Variationmentioning
confidence: 99%
See 2 more Smart Citations
“…4. a, Comparison of an 13 C NMR spectrum (HPE in DMF [45]) and the predicted degree distribution for the system with A 2 :B 3 = 1:1 at p A = 0.93. b, Comparison of the phenolic unit degree distribution (only out-edges) in a phenol-methylene system predicted by MD (dots) simulation [30] to the theory (solid lines). The gel point is predicted at p A = 0.58 by the MD simulation, the theory predicts it at p A = 0.5.…”
Section: The Time Variationmentioning
confidence: 99%
“…[45], and also, for a different polymerisation system, against Molecular Dynamics (MD) simulation data from Ref. [30].…”
Section: The Time Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…Following bond formation, as proposed by Izumi et al, bond angles are checked to determine whether the angle is realistic: bonds with unrealistic angles (< 90 • ) are broken [29]. Note that the bond angle used is the methylene bridge angle, rather than using the angle defined across the phenol rings before bonding.…”
Section: Script Iterationsmentioning
confidence: 99%
“…A key focus across all simulations of thermosets is enabling a high degree of crosslinking within short runtimes. Izumi et al have demonstrated extensively the potential for MD within phenolic resin research [27][28][29]. They have shown that large (>200,000 atom, or 10,000 phenol molecules) MD simulations are suitable for modelling phenolic resins for studying inhomogeneity.…”
Section: Introductionmentioning
confidence: 99%